2021
DOI: 10.21608/jfds.2021.97427.1028
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Egyptian Catfish (Clarias gariepinus) Fillet During Frozen Storage تقييم جودة فيليه سمک القراميط المصرى (Clarias gariepinus) اثناء التخزين المجمد

Abstract: Biochemical assay, microbial load determination, and sensory evaluation of Egyptian Catfish fillets were examined during frozen storage at -18 ºC up to 12 months. The initial chemical composition of Catfish fillet was moisture 73.01%, protein 80.96%, Crude oil 09.52%, crude ash 7.30%, and total carbohydrate 2.11%. The frozen storage process showed a significant effect on the chemical composition of studied Catfish fillets. pH and WHC values were decreased significantly whereas the TVBN and TBA values significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
4
1
0
Order By: Relevance
“…According to the (EOS, 1991), 30 mg/100g sample is the allowed upper limit of TVB-N and 10 mg/100g sample is the allowed upper limit of TMA. The above mentioned results are in agreement with those obtained by Hamad, (2021), who reported that TVBN and TMAN in raw catfish fillets (Clarias gariepinus) were 13.40 and 1.02 mg/100g and (Mahmoud et al (2021) showed that, frozen catfish fillet during the storage period up to 12 months, the TVB-N value increase Quality Properties of African Catfish (Clarias Gariepinus)… from 22.02 to 24.27 mg/100g. Moreover, Mohamed (2016) showed that, the total volatile basis nitrogen (TVB.N) and trimethylamine (TMA) value for fresh Catfish were 6.55 and 3.696 mg/100g; respectively.…”
Section: Physicochemical Properties Of Black and Gray Catfish Filletsupporting
confidence: 91%
See 4 more Smart Citations
“…According to the (EOS, 1991), 30 mg/100g sample is the allowed upper limit of TVB-N and 10 mg/100g sample is the allowed upper limit of TMA. The above mentioned results are in agreement with those obtained by Hamad, (2021), who reported that TVBN and TMAN in raw catfish fillets (Clarias gariepinus) were 13.40 and 1.02 mg/100g and (Mahmoud et al (2021) showed that, frozen catfish fillet during the storage period up to 12 months, the TVB-N value increase Quality Properties of African Catfish (Clarias Gariepinus)… from 22.02 to 24.27 mg/100g. Moreover, Mohamed (2016) showed that, the total volatile basis nitrogen (TVB.N) and trimethylamine (TMA) value for fresh Catfish were 6.55 and 3.696 mg/100g; respectively.…”
Section: Physicochemical Properties Of Black and Gray Catfish Filletsupporting
confidence: 91%
“…This is an extensive characteristic for many reasons: From the point of economical view, weight reduction due to water loss is of very importance (Olsson et al, 2003), The accumulation of discharge is unattractive to consumers and loss of water is negatively affected the muscle texture (Abd El-latif, 2021). The obtained results agreement comparatively with that of Paleckaitis et al (2018); Abd-Elfttah (2021) and Mahmoud et al (2021) for catfish fillet. According to data in Table ( 6), the TBA value in both black and gray catfish fillet was 0.85 mg malonaldehyde / kg, while it was 0.80 mg malonaldehyde / kg gray color catfish fillet and that reflect the relatively high fat content in black catfish meat.…”
Section: Physicochemical Properties Of Black and Gray Catfish Filletsupporting
confidence: 91%
See 3 more Smart Citations